CRISPR/Cas9 suppression of OsAT10, a rice BAHD acyltransferase, reduces p-coumaric acid incorporation into arabinoxylan without increasing saccharification - Möller, Svenning R.; Lancefield, Christopher S.; Oates, Nicola C.; Simister, Rachael; Dowle, Adam; Gomez, Leonardo D.; McQueen-Mason, Simon J. (Frontiers in Plant Science, 2022)
Ester-linked hydroxycinnamic acids ferulic acid (FA) and para-coumaric acid (p-CA) play important roles in crosslinking within cell wall arabinoxylans (AX) and between AX and lignin in grass cell walls. The addition of hydroxycinnamates to AX, is mediated by the Mitchell clade of BAHD acyl-coenzyme A-utilizing transferases. Overexpression of OsAT10 (a Mitchell clade BAHD acyl transferase) in rice, has previously been shown to increase p-CA content in AX in leaves and stems, leading to increased cell wall digestibility, potentially associated with a concomitant decrease in FA content. To investigate the physiological role of OsAT10 we established CRISPR/Cas9 rice knock-out mutants devoid of OsAT10. Our analysis of hydroxycinnamic acid content in wild type plants revealed that AX associated p-CA is found almost exclusively in rice husks, with very little found in other tissues. Mutant plants were essentially devoid of ester-linked p-CA associated with AX, indicating that OsAT10 represents the major enzyme responsible for the addition of p-CA to arabinoxylan in rice plants. We found no change in the digestibility of rice husk lacking AX-associated p-CA, suggesting that the changes in digestibility seen in OsAT10 overexpressing plants were solely due to compensatory decreases in AX-associated FA.